2011
DOI: 10.1080/00028487.2011.584489
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Reproductive Success of Steelhead from a Hatchery Supplementation Program (Little Sheep Creek, Imnaha Basin, Oregon)

Abstract: Hatchery supplementation programs are designed to enhance natural production and maintain the fitness of the target population; however, it can be difficult to evaluate the success of these programs. Key to the success of such programs is a relatively high reproductive success of hatchery fish. This study investigated the relative reproductive success (RRS) of steelhead Oncorhynchus mykiss (anadromous rainbow trout) by creating pedigrees for hatchery and natural spawning steelhead. We genotyped adult steelhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 45 publications
6
86
2
Order By: Relevance
“…They found that migrant offspring produced by migrant fish had a greater proportion of returns than migrant offspring from resident fish, suggesting migrants are inheriting alleles that promote ocean survivability. In contrast, the Little Sheep Creek samples were collected from an area where migratory and resident life history types coexist providing greater opportunity for mating between the life history types (Berntson et al 2011) as confirmed by the few loci associated with migration/residency, few F ST outliers, low levels of LD, largely neutral Tajima’s D values, and low numbers of private alleles. Similar low levels of F ST and few outliers are found in other populations of O. mykiss where residents and migrants co-occur (Limborg et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that migrant offspring produced by migrant fish had a greater proportion of returns than migrant offspring from resident fish, suggesting migrants are inheriting alleles that promote ocean survivability. In contrast, the Little Sheep Creek samples were collected from an area where migratory and resident life history types coexist providing greater opportunity for mating between the life history types (Berntson et al 2011) as confirmed by the few loci associated with migration/residency, few F ST outliers, low levels of LD, largely neutral Tajima’s D values, and low numbers of private alleles. Similar low levels of F ST and few outliers are found in other populations of O. mykiss where residents and migrants co-occur (Limborg et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…All migrants sampled were downstream of these waterfalls, whereas all residents sampled were upstream (see Thrower et al 2004 for more details). The migrant and resident individuals in the Little Sheep Creek population are not separated by barrier waterfalls (see Berntson et al 2011 for more details) and so samples of both phenotypes were taken from the same area. Resident trout from the Little Sheep Creek, Oregon, population were determined to be resident as determined by size threshold (minimum fork length of 160 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Examining the Columbia River restoration program, in light of river restoration in general, provides insights into factors underpinning successful activities (e.g., improved survival at dams for juvenile salmonids) (34) as well as less successful efforts (35). The Northwest Power and Conservation Council (NPCC) Fish and Wildlife Program for the Columbia River seeks to establish and maintain an ecosystem that sustains an abundant, productive, and diverse community of fish and wildlife (36).…”
Section: Settingmentioning
confidence: 99%
“…One management action is recycling, where collected adults are released back to fisheries for additional angling opportunity (Lindsay et al 2001, Kock et al 2016. However, any SRS not harvested or recollected could increase competition for mates on spawning grounds, spawn with other hatchery-produced fish, or hybridize with endemic conspecifics locally or after straying to other basins (Araki et al 2007, Berntson et al 2011. However, any SRS not harvested or recollected could increase competition for mates on spawning grounds, spawn with other hatchery-produced fish, or hybridize with endemic conspecifics locally or after straying to other basins (Araki et al 2007, Berntson et al 2011.…”
Section: Introductionmentioning
confidence: 99%